2012
DOI: 10.3758/s13421-012-0214-4
|View full text |Cite|
|
Sign up to set email alerts
|

Citation rates for experimental psychology articles published between 1950 and 2004: Top-cited articles in behavioral cognitive psychology

Abstract: From citation rates for over 85,000 articles published between 1950 and 2004 in 56 psychology journals, we identified a total of 500 behavioral cognitive psychology articles that ranked in the top 0.6 % in each half-decade, in terms of their mean citations per year using the Web of Science. Thirty nine of these articles were produced by 78 authors who authored three or more of them, and more than half were published by only five journals. The mean number of cites per year and the total number of citations nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The same indicator, but named differently "PP(10%)", is applied in the CWTS Leiden ranking 4 better explained in Waltman et al (2012). This perspective in analyzing excellence has also stimulated numerous studies focused on specific sub-fields, both in the hard sciences (for example environmental sciences, Khan & Ho, 2012;or urology, Hennessey, Afshar & MacNeily, 2009) and in social sciences (for psychology, in Cho, Tse & Neely, 2012;for law, Shapiro, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The same indicator, but named differently "PP(10%)", is applied in the CWTS Leiden ranking 4 better explained in Waltman et al (2012). This perspective in analyzing excellence has also stimulated numerous studies focused on specific sub-fields, both in the hard sciences (for example environmental sciences, Khan & Ho, 2012;or urology, Hennessey, Afshar & MacNeily, 2009) and in social sciences (for psychology, in Cho, Tse & Neely, 2012;for law, Shapiro, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…One recent analysis of citations from 1956-2004 using the Web of Science reported that both Lavie and Lavie et al are in the top 500 articles in the cognitive psychology literature published between 1950 and 2004. 21 We conducted a separate Web of Science citation analysis of the four core LT articles. 15,16,22,23 Between 1994 and 2013 these articles have collectively been cited 1825 times, equaling a combined annual citation rate of 92.95 citations/year (total citations/20 years).…”
Section: Introductionmentioning
confidence: 99%
“…One recent analysis of citations from 1956–2004 using the Web of Science reported that both Lavie and Lavie et al . are in the top 500 articles in the cognitive psychology literature published between 1950 and 2004 . We conducted a separate Web of Science citation analysis of the four core LT articles .…”
mentioning
confidence: 99%
“…Our finding that women are under-represented in positions of leadership (editors-in-chief, or recipients of distinguished career awards) may beg the question of whether there are gender differences in productivity that could account for the disparities observed. Perhaps women in cognitive psychology simply are less productive and therefore do not garner professional recognition to the same degree as their male counterparts (see Cho, Tse, & Neely, 2012, for an analysis of the top cited publications from 1950 to 2004 in cognitive psychology). Because we do not have current data on gender differences in publication output, quality or citation impact among cognitive psychologists, this question cannot fully be addressed.…”
Section: Discussionmentioning
confidence: 99%